Constraints on the geometry of the suasselkä post-glacial fault, northern finland, based on reflection seismic imaging - Abdi, A.; Heinonen, S.; Juhlin, Christopher; Karinen, T. (Elsevier, 2015)
Unloading of the ice during the last glacial period in northern Fennoscandia is believed to have generated major faulting. These faults, often referred to as post-glacial faults, typically have clear surface exposures, but their geometry at depth is poorly known. In order to better understand the geometry at depth of the Suasselkä post-glacial fault in Finland, three high resolution 2D reflection seismic profiles over the fault were reprocessed. Their total profile length is about 60 km and they were acquired as part of a major effort in Finland to map the uppermost crust in mining areas. The reprocessing led to significantly improved images that could be used to map the fault at depth. Two approximately N–S striking profiles and one E–W striking profile were reprocessed. The different azimuths and the crooked nature of the profiles allowed the fault geometry to be relatively well constrained. Clear reflections from the fault, dipping towards the SE, can be traced from the shallow subsurface down to about 3 km. The strike and dip of two sets of dipping reflections in the stacked data along with geometrical constraints and cross-dip analysis give a consistent dip of about 35–45° towards the SE for the fault. The strike and dip vary from N55E with a dip of 35° in the east to a strike of N48E with a dip of 45° in the west. Existence of the two sets of reflections indicates that the fault surface is non-planar. Aside from allowing the geometry of the fault to be determined, the seismic data show a complex reflectivity pattern in the area and indications of both reverse and normal movement along fault planes with similar orientation to the Suasselkä post-glacial fault. These images can be used as a basis for better characterizing the 3D geology of the area.